Trends in prevalence of hypertension in Brazil: a systematic review with meta-analysis. - Rafael V Picon; Flávio D Fuchs; Leila B Moreira; Glaube Riegel; Sandra C Fuchs (PLoS ONE)
Background The prevalence of hypertension in emerging nations was scarcely described to date. In Brazil, many population-based surveys evaluated the prevalence in cities throughout the country. However, there is no population-based nationwide study of prevalence of hypertension. In this study, we estimated the prevalence of hypertension for the country and analyzed the trends for the last three decades. Methods Cross-sectional and cohort studies conducted from 1980 to 2010 were independently identified by two reviewers, without language restriction, in the PubMed, Embase, LILACS, and Scielo electronic databases. Unpublished studies were identified in the Brazilian electronic database of theses and in annals of Cardiology congresses and meetings. In total, 40 studies were selected, comprising 122,018 individuals. Results Summary estimates of prevalence by the former WHO criteria (BP≥160/95 mmHg) in the 1980's and 1990's were 23.6% (95% CI 17.3-31.4%) and 19.6% (16.4-23.3%) respectively. The prevalence of hypertension by the JNC criteria (BP≥140/90 mmHg) in the 1980's, 1990's and 2000's were 36.1% (95% CI 28.7-44.2%), 32.9% (29.9-36.0%), and 28.7% (26.2-31.4%), respectively (P<0.001). In the 2000's, the pooled prevalence estimates of self-reported hypertension on telephone inquiries was 20.6% (19.0-22.4%), and of self-reported hypertension in home surveys was 25.2% (23.3-27.2%). Conclusions The prevalence of hypertension in Brazil seems to have diminished 6% in the last three decades, but it still is approximately 30%. Nationwide surveys by self-reporting by telephone interviews underestimate the real prevalence. Rates of blood pressure control decreased in the same period, corresponding currently to only one quarter of individuals with hypertension.